Anc Compliance As Viewed From The Knowledge Of Pregnant Women About The Danger Signs Of Pregnancy Trimester Iii In The The Ngambon Health Center Bojonegoro - Anik Puji Lestari; Anggrawati Wulandari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2023)
The high number of ANC non-adherence in pregnant women due to the lack of knowledge of pregnant women about the danger signs of third trimester pregnancy causes pregnant women to be reluctant to visit antenatal care to prevent and recognize the danger signs of pregnancy and seek health help to avoid morbidity and mortality. The purpose of this study was to analyze ANC compliance in terms of the knowledge of pregnant women about the danger signs of third trimester pregnancy in the working area of ​​Ngambon Health Center, Bojonegoro Regency. In this study using an observational analytic design with cross sectional approach. The population in this study were 33 respondents with a sample size of 30 respondents. The sample in this study were all pregnant women in the working area of ​​the Ngambon Community Health Center in Bojonegoro Regency with a sampling method using simple random sampling technique. Data collection using questionnaires and medical records (MCH Handbook). Bivariate analysis to see the relationship between the independent variables with the dependent variable using the statistical coefficient contingency test with a significant level α = 0.05. The results showed there was a relationship between the knowledge of pregnant women about the danger signs of third trimester pregnancy with ANC compliance in the working area of ​​Ngambon Puskesmas, Bojonegoro District, with a P value of 0.005 <α (0.05) and r = 0.509, so H0 was rejected and H1 accepted, which means that there is a relationship between the knowledge of pregnant women about the danger signs of third trimester pregnancy with ANC compliance in Ngambon Health Center, Bojonegoro Regency, and the level of close relationship. Knowledge of pregnant women about the danger signs of trimester III pregnancy greatly affect ANC compliance in pregnant women.